2014
DOI: 10.1155/2014/784863
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Zn, Cu, and Fe Content in Hair and Serum in Alopecia Areata Patients with Normal Group

Abstract: Background. Alopecia areata (AA) is an autoimmune condition, in which hair is lost from some areas of the body. Though its etiopathogenesis is not fully understood, there are claims that imbalance of trace elements may trigger the onset of AA, by distorting immune functions. In this study, we tried to investigate the relationship between AA and iron, zinc, and copper levels of serum and hair. Materials and Methods. Sixteen female patients with AA (14–40 years old) and 27 healthy female controls were enrolled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 10 publications
1
25
1
Order By: Relevance
“…In one study [56] of 27 AA patients from Iran, serum and hair copper levels were lower in AA patients compared to controls. However, all other studies [54, 55, 57, 58] of serum copper levels identified no differences between AA patients and controls. Two of these studies [55, 58] also found no differences in magnesium levels.…”
Section: Micronutrientsmentioning
confidence: 85%
See 2 more Smart Citations
“…In one study [56] of 27 AA patients from Iran, serum and hair copper levels were lower in AA patients compared to controls. However, all other studies [54, 55, 57, 58] of serum copper levels identified no differences between AA patients and controls. Two of these studies [55, 58] also found no differences in magnesium levels.…”
Section: Micronutrientsmentioning
confidence: 85%
“…Two other small case-control studies [55, 56] found lower serum zinc levels in AA patients compared to controls. In contrast to these studies, two [57, 58] case-control studies from Finland (27 AA cases) and Iran (16 AA cases) found no difference in serum zinc levels of AA patients versus controls. The study from Finland revealed minimal differences in serum, red-cell, or 24-hour urine zinc concentrations compared to the general Finish population [58].…”
Section: Micronutrientsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the association between AA and Zn deficiency seems contradictory, given that AA is an autoimmune disease, whereas Zn deficiency generally results in an impaired immune response [74,75]. In support of this association, some past studies have found no decreased serum Zn levels in AA patients [76][77][78]. In contrast, in the 2000s, several studies found decreased serum Zn levels in AA patients [60,[79][80][81][82].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Zinc also cause modulation of the activity of type 1 and 25α reductase. [11,12] Study by Otberg et al (2007) reported that the prevalence increases with age. Where 53% of men who age 40-49 years showed hair loss symptoms is moderate until severe according to the Hamilton degree grade 3 or more.…”
Section: Discussionmentioning
confidence: 99%